TRANSABDOMINAL PREPERITONEAL ALLOPLASTY OF INGUINAL HERNIAS USING A NANOMODIFIED MESH IMPLANT - Lutkovskyi, R.A.; Chelischvili, A.L. (World of Medicine and Biology, 2022)
Surgical treatment of 142 patients with inguinal hernias who underwent transabdominal preperitoneal allohernioplasty was analyzed. The author’s mesh was used in group I patients, and in group II patients, a classical polypropylene mesh was used. Statistically, significantly better results were obtained in patients of group I compared with group II: seroma was found in 1.4 % and 7.0 % of patients, respectively. Chronic pain was observed in 5.6 % of patients in group II compared to group I, with no such complications, hernia recurrence – in 8.5 % and 1.4 % of patients, respectively. The duration of inpatient treatment in group I was 2.3±1.2 days, in group II – 5.2±1.1 days. Surgical treatment of inguinal hernias using nanomodified polypropylene mesh was more effective than using classical polypropylene mesh, as evidenced by a decrease in the seroma frequency from 7.0±1.3 to 1.4±0.3 %, chronic postoperative pain – from 5.6±0.2 to 0 %, hernia recurrence – from 8.5±0.3 to 1.4±0.2 %.